Negotiation of Meaning in the Participatory Culture Communication Practices of the Carat Medan Community - Yunita Ayu Syahputri NST; Sigit Hardiyanto (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2026)
The rapid changes in popular culture trends on social media often cause fan communities to shift quickly and not last long. However, the Carat Medan community has been able to endure for nearly a decade. This study analyzes how the negotiation of meaning within participatory culture communication practices in the Carat Medan community functions as a strategy to maintain the community's existence from 2017 to 2026. The research method using a field study. Data were collected through structured interviews, documentation studies, and participant observation across various community activities. The findings show that the sustainability of Carat Medan is driven by a the community collective ability to negotiate the meanings of messages and values, which are then aligned with the local cultural context. This process encourage the transformation of fans from active consumers into prosumers who contribute to the producing community activities and collaborating with local media. This study concludes that communicative flexibility, the creation of a safe third space for interaction, and a strong participatory culture enable the community to remain cohesive and to navigate internal dynamics despite ongoing changes in social media trends.